The Island Of Missing Trees - Shafak,Elif; Elif Shafak (London Penguin Books, 2021)
ummary: "A rich, magical new novel on belonging and identity, love and trauma, nature and renewal, from the Booker-shortlisted author of 10 Minutes 38 Seconds in This Strange World. Two teenagers, a Greek Cypriot and a Turkish Cypriot, meet at a taverna on the island they both call home. In the taverna, hidden beneath garlands of garlic, chili peppers and creeping honeysuckle, Kostas and Defne grow in their forbidden love for each other. A fig tree stretches through a cavity in the roof, and this tree bears witness to their hushed, happy meetings and eventually, to their silent, surreptitious departures. The tree is there when war breaks out, when the capital is reduced to ashes and rubble, and when the teenagers vanish. Decades later, Kostas returns. He is a botanist looking for native species, but really, he's searching for lost love. Years later a Ficus carica grows in the back garden of a house in London where Ada Kazantzakis lives. This tree is her only connection to an island she has never visited--- her only connection to her family's troubled history and her complex identity as she seeks to untangle years of secrets to find her place in the world. A moving, beautifully written, and delicately constructed story of love, division, transcendence, history, and eco-consciousness, The Island of Missing Trees is Elif Shafak's best work yet"-- Provided by publisher.
Keywords: Turkish fiction